Monitoring terhadap Kebijakan Penerimaan Peserta Didik Baru Tingkat SMA di Kabupaten Pamekasan dalam Perspektif Zoning - Widya Rahmi, Nur (Jurnal Ilmiah Administrasi Publik, 2022)
This research is motivated by the various problems that arise in Indonesia, especially in Pamekasan Regency regarding the Admission of New Student Participants which uses a zoning system in the 2018/2019 school year and in the 2019/2020 school year. This study aims to determine the factual premise that exists in the field related to PPDB in the two periods by monitoring the policy of new high school student admissions in Pamekasan Regency in a zoning perspective. This study uses qualitative research methods that aim to explore data in depth. This research is expected to be a material for the government to make a strategic decision in the future related to PPDB in the zoning perspective in Pamekasan Regency.